Point-of-care faecal calprotectin testing in patients with paediatric inflammatory bowel disease during the COVID-19 pandemic. Issue 1 (4th May 2021) - Jere, Mwansa; Garrick, Vikki; Curtis, Lee; Tayler, Rachel; Gervais, Lisa; Gerasimidis, Konstantinos; Hansen, Richard
Abstract : Objectives: Following the disruption of normal paediatric inflammatory bowel disease (IBD) services during the peak of the COVID-19 pandemic, we prospectively audited the first-time use of home faecal calprotectin testing. We aimed to provide an alternative to laboratory tests and to assess the value of home testing as part of our regular services going forward. Methods: Home test kits as well as accompanying user instructions were made available to our patients with paediatric IBD that required faecal calprotectin test between 17 April and 12 August 2020. Once the user completed the test, results were automatically uploaded to the result portal and clinical staff were alerted. A user feedback questionnaire was sent to users that had completed the home test. Results: Of the 54 patients, 41 (76%) aged between 4.7 and 18.1 years used the home test. A total of 45 home tests were done, one of which produced an invalid result. The decision to modify management was made in 12 (29%) of the patients, while 14 (34%) had no changes made and 15 (37%) required further assessment. Twenty (48.8%) responded to the questionnaire and 85% stated that they preferred the home test to the laboratory testing method. Conclusions: Home calprotectin tests were useful in guiding clinical management during a time when laboratory testing was less available. They may offer benefits as part of routine paediatric IBD monitoring to help target appointments and reduce unnecessary hospital attendances in the future.